Sasun - McCarthy, Justin, 1945- (My University, 2014)
The standard narrative of the Sasun rebellion is thus: Kurds invaded, attempted to extort Armenians, Armenians would not pay, battles ensued, Armenians won, the Sultan was incensed and sent thousands of regular soldiers and special battalions to punish the Armenians, with 1,000 – 16,000 Armenians perishing and suffering brutalities such as rape and infanticide
The history of an 1890s Armenian revolt
Justin McCarthy, Ömer Turan, and Cemalettin Taşkiran. - Salt Lake City : University of Utah Press, 2014. - xiii, 351 pages : ill., maps ; 24 cm. - Includes bibliographical references and index
Տվյալները՝ ինտերնետային կայքից
https://www.pdfdrive.com/sasun-the-history-of-an-1890s-armenian-revolt-e166620910.html
Contents; Figures; A Note on Translations and Transliterations; Acknowledgments; Introduction; 1. Sasun; 2. Conflict in Sasun; 3. Sasun in the Press; 4. The Missionaries; 5. Publicists for the Armenian Cause; 6. The British and Others; 7. The Commission I; 8. The Commission II; 9. Conclusion; APPENDIX A: The Hallward Report; APPENDIX B: The Testimony of Colonel Tevfik; APPENDIX C: Report of the Consular Delegates; APPENDIX D: The Hampson Report; Bibliographical Note; Notes; Selected Bibliography; Index
Keywords: Armenians-Turkey-History; Kurds-Turkey-History; Ethnic conflict-Turkey; Sason-History